The Attitude of Women on the Manufacturing of the Indonesian Ulama Council of North Sumatra Regarding the Documentary Video of the Polemic of Polygamy in Indonesia: Sharing Heaven on Vice Indonesia's Youtube Channel - Yogo Pamungkas L Tobing; Iskandar Zulkarnain; Nurbani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the cognitive, affective and conative responses of women administrators of the North Sumatra Indonesian Ulema Council (MUI) to the documentary video